Incidencia de la comunicación interna en el clima laboral del cuerpo de bomberos del cantón Pujilí en el período 2022- 2023 - Chimbo Moposita, Johanna Isabel (2023)
The objective of this research work was to analyze the incidence of internal communication in the work environment of the Pujilí Canton Fire Department in the period 2022-2023, given that the communication between boss and collaborator must be optimal, in the case study. There were certain differences between the administrative and operational area. For the fulfillment of the work, the inductive methodology with a quantitative approach was used, through the application of two previously validated questionnaires, the first prepared by the Great Place To Work Trust, focused on measuring internal communication with dimensions such as organizational communication, communication in the area , vertical communication, horizontal communication, formal and informal communication, communication barriers, information technologies and ethical communication. The second instrument aimed at measuring the work environment prepared by Bello (2017) addressed dimensions such as credibility, respect, impartiality, leadership and infrastructure.